Vulnerability and Factors Affecting Public Health Resilience Related to Clean Water Sanitation in Coastal Areas, Muara Gembong District, West Java - Dwi Atmanto; Elvyra Yulia; Eti Herawati (Dinasti International Journal of Education Management And Social Science, 2025)
Located on the northern coast of Java near Jakarta, Muara Gembong is confronted with significant environmental health threats due to land control issues, land conversion, and pollution from the Citarum River. These factors contribute to poor water quality in residential areas, making the water unsuitable for clean water use. The objective of this study is to investigate the vulnerability and factors influencing the health resilience of populations who rely on groundwater. The research utilizes qualitative and quantitative correlational methods, gathering data from 40 respondents in Pantai Mekar Village, Muara Gembong, West Java, through questionnaires. Three proposed hypotheses were processed using SPSS. The findings reveal that environmental health in Muara Gembong, particularly sanitation and clean water access, remains a significant problem, leading to increased vulnerability to infectious diseases. Key discoveries include a substantial relationship between knowledge of groundwater quality and community health resilience (0.000 < 0.05), a link between water sanitation attitude in coastal areas and health resilience (0.002 < 0.05), and a combined effect of groundwater quality knowledge and sanitation attitude on health resilience (0.001 < 0.05). Collectively, groundwater quality knowledge and sanitation behavior contribute 36.5% to the health resilience of coastal groundwater users.